Strategi Penyaluran Dana Zakat di Badan Amil Zakat Nasional Kabupaten Padang Pariaman - Reffa Amanda Pratama; Asrida Asrida (ZAWA: Management of Zakat and Waqf Journal, 2024)
The National Zakat Amil Agency (BAZNAS) Padang Pariaman Regency is a non-structural government institution that is independent and responsible for managing zakat based on Islamic law. This research focuses on the formulation, implementation and evaluation of zakat fund distribution strategies at BAZNAS Padang Pariaman Regency. This research uses a field research method with a qualitative descriptive approach. Data was obtained through interviews with the Chair of BAZNAS, Deputy Chair II, and the BAZNAS Distribution and Utilization sector. Data were analyzed through the stages of reduction, presentation and drawing conclusions. Research Results: The formulation of the BAZNAS Strategy for Padang Pariaman Regency follows the distribution pattern of the National Zakat Amil Agency (BAZNAS) of the Republic of Indonesia, which is included in the Annual Activity and Budget Plan (RKAT) and Standard Operating Procedures (SOP) for Distribution and Utilization. Strategy Implementation Strategy implementation is carried out according to SOPs through various programs with strict administrative procedures and thorough verification. Strategy Evaluation Evaluation is carried out on the vision, RKAT achievements, and Key Performance Indicators (KPI) to ensure program efficiency and effectiveness, measure impact, and develop improvement strategies in the future.